2018
DOI: 10.1002/btpr.2606
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of EuWRI1, encoding a transcription factor in E. ulmoides, changes the seeds oil content in transgenic tobacco

Abstract: The WRINKLED1 (WRI1) gene is a well-established key transcriptional regulator involved in the regulation of fatty acid biosynthesis in developing seeds. In this study, a new WRI1 gene was isolated from seeds of Eucommia ulmoides and named EuWRI1. A close link between gibberellins signaling and EuWRI1 gene expression was suggested in this study. Functional characterization of EuWRI1 was elucidated through seed-specific expression in tobacco. In transgenic tobacco, the expression of EuWRI1 in eight independent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…A study showed that tobacco seeds have oil contents of about 30–40%, which is higher than that of some other oil crops, including soybean, cotton, and olive [ 4 ]. Tobacco seed oil contains a variety of beneficial substances, such as triacylglycerols, phospholipids, tocopherols, sterols, and unsaturated fatty acids [ 5 ]. In addition, the major unsaturated fatty acids in tobacco seed oils are linoleic acid, oleic acid, palmitic acid, and stearic acid [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that tobacco seeds have oil contents of about 30–40%, which is higher than that of some other oil crops, including soybean, cotton, and olive [ 4 ]. Tobacco seed oil contains a variety of beneficial substances, such as triacylglycerols, phospholipids, tocopherols, sterols, and unsaturated fatty acids [ 5 ]. In addition, the major unsaturated fatty acids in tobacco seed oils are linoleic acid, oleic acid, palmitic acid, and stearic acid [ 6 ].…”
Section: Introductionmentioning
confidence: 99%